مستقبل النفط في سورية وانعكاساته على الاقتصاد الوطني - محمود يوسف; عروس محمد; اسما عيل عدنان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث مستقبل الاقتصاد السوري في ظل الدراسات المتواترة التي تؤكد على انخفاض إنتاج النفط في سورية مستقبلا ، ففي البداية يحاول إلقاء الضوء على الإنتاج السوري المتوقع من النفط الخام في الفترة ما بين 2006 – 2020 ، ثم ينتقل لدراسة تأثيرات انخفاض إنتاج النفط الخام في شقين : شق متعلق بالقطاع النفطي نفسه،، وشق آخر متعلق بالاقتصاد الوطني ككل من خلال انخفاض الإيرادات الحكومية وتأثيراتها اللاحقة في قدرة الدولة على أداء مهامها. وفي النهاية يطرح البحث مجموعة مقترحات يمكن أن تساعد في التخفيف من آثار انخفاض إنتاج النفط الخام في المستقبل: كتطوير مصافي النفط لزيادة عائداتها عند نفس مستوى الإنتاج ، تعديل النظام الضريبي ، وتخفيف الهدر في مؤسسات القطاع العام ، وتطوير الاستثمارات وتوجيهها نوعيا ، مع محاولة شرح موجز لكل خيار من هذه الخيارات . The study tackles the future of the Syrian economy in the light of the fluctuating studies, which confirms the decrease of petroleum product in Syria in. Firstly, it throws light on the estimated Syrian production from 2006 to 2020. The then study deals with the effect of the reduction of crude oil production in two splits: one split concerns the petroleum sector itself, the other concerns the national economy as a whole at a time of decrease of governmental revenue and its subsequent effect regarding the ability of the government to carry out its duties. Finally the study raises various suggestions that may help to check the result of the reduction in crude oil production in the future, such as modifying the tax system, reducing the losses of public sector establishment and developing oil refineries.